Using new digital technologies in employee training to avoid occupational accidents in the industry - Muresan Petru Iulian; Milosan Ioan; Machedon-Pisu Teodor; Reit Adrian; Senchetru Dorin; Oancea Gheorghe (MATEC Web of Conferences, 2021)
The most frequent workplace accidents in the industry are most of the times caused by the employer’s failure to fulfill their obligation to provide appropriate on-the-job training. Starting from this state of affairs, this paper analyzes the main cause of workplace accidents in the industry, which is the lack of training, or incomplete or inadequate training of employees, a situation indicated by the latest studies and the latest activity report of Labor Inspectorate. The solution identified by most employers was to use the online environment, this being the only way that allows the achievement of both of the aforementioned objectives at the same time. In this context, the paper identifies and proposes the use of the online environment, especially in the process of distance training of workers, giving them the opportunity to receive training documents, to analyze them, to electronically sign them and send them to the employer in electronic format. This proposal of supplementing the current legislation with the possibility of using the online environment in the field of occupational health and safety (OHS) also takes into account other categories of benefits that this solution brings, such as streamlining OHS and optimizing costs incurred in fulfilling these legal obligations.